Assessing the risk of attack in the management of asthma: a review and proposal for revision of the current control-centred paradigm. - Blakey, J; Woolnough, K; Fellows, J; Walker, S; Thomas, M; Pavord, I (2013)
Asthma guidelines focus on day-to-day control of symptoms. However, asthma attacks remain common. They continue to cause mortality and considerable morbidity, and are a major financial burden to the UK National Health Service (NHS) and the wider community. Asthma attacks have chronic consequences, being associated with loss of lung function and significant psychological morbidity. In this article we argue that addressing daily symptom control is only one aspect of asthma treatment, and that there should be a more explicit focus on reducing the risk of asthma attacks. Management of future risk by general practitioners is already central to other conditions such as ischaemic heart disease and chronic renal impairment. We therefore propose a revised approach that separately considers the related domains of daily control and future risk of asthma attack. We believe this approach will have advantages over the current 'stepwise' approach to asthma management. It should encourage individualised treatment, including non-pharmacological measures, and thus may lead to more efficacious and less harmful management strategies. We speculate that this type of approach has the potential to reduce morbidity and healthcare costs related to asthma attacks.